Pendampingan Orang Tua Dengan Metode Project Based Learning - Iqfa Qonitah Febiani (Yayasan Literasi Sains Indonesia, 2022)
Covid-19 really has an impact on different lifestyles ranging from the economy, health, and education. The impact of Covid-19 on the world has made all meeting activities a distance education system, including in a world that causes direct learning meeting activities to turn into remote (online) activities. Assistance to parents in the brave school learning process for children during the pandemic is needed to help children continue school activities independently. with the Project-Based Learning method, it is easier for parents to work collaboratively and collaborate with each other. The learning system makes learning more fun, creative, and makes children active with each other to share thoughts